Femtosecond laser-induced iridescent effect on AZ31B magnesium alloy surface - Guan, Ying Chun (2016)
Both micro-ripples and nano-ripples were firstly reported at AZ31B magnesium alloy surface irradiated by femtosecond laser in atmospheric environment. Iridescent effect was also demonstrated over a large area of the irradiated surface induced by scanning laser beam. Results revealed that the colour effect was mainly attributed to the nano-ripples with broad distribution of periods acting as diffraction gratings, and intensity of the structural colour was greatly influenced by morphology evolution of the micro-ripples with laser processing. It was suggested that near-field interference between surface plasmons polaritons and incident laser light determined the formation of the nano-ripples, and initial surface roughness combing with such interference lead to the formation of the micro-ripples. Potential applications of such effect on Mg alloys and how to apply the technique to other materials with different properties was further proposed.